Intimate Partner Violence in Honduras: Ecological Correlates of Self-Reported Victimization and Fear of a Male Partner - Wheeler, Jennifer (Journal of interpersonal violence, 2021)
The experience of intimate partner violence (IPV) is influenced by individual, relationship, community, and societal-level factors, including the prevalence and acceptance of societal violence in which the victim lives. These factors transcend a woman’s present circumstances and personal history and the gender and power relationships within her household. This is particularly relevant in Honduras, where a high level of IPV occurs within a traditionally patriarchal society and growing societal violence and crime. This study examines the factors—informed by a social ecological theoretical perspective—associated with the experience of IPV. We use data from the Honduras Demographic and Health Survey (ENDESA) 2011–2012 to estimate multilevel, multivariate models predicting the likelihood that a woman experiences emotional, physical, and/or sexual IPV and/or fear of her partner. Our models contain higher level contextual effects that capture regional variations in social violence and aggregated norms capturing acceptance of IPV. We find that a woman’s likelihood of experiencing violence is related to individual, relationship, and household-level characteristics, including marital status, age at first cohabitation, employment status, violence within the parental home, women’s accepting attitudes toward IPV, autonomy in decision-making, partner’s use of alcohol, the nature of the relationship with her partner (i.e., living together or not), and educational and age differences with her partner. Notably, women living in more violent areas—measured by violence statistics and aggregate community-level norms regarding spouse beating—were more likely to experience IPV. These findings contribute to our understanding of the risk of IPV and to the evidence that can be used to identify the most vulnerable women and opportunities for intervention to prevent further victimization. By using an analytical methodology that reflects the complexity of factors that place women at risk for IPV, we can isolate, address, and advocate for changing circumstances that make Honduran women vulnerable to IPV.